2023
DOI: 10.1002/jsfa.12796
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 and ochratoxin A reduction by Lactobacillus spp. during bread making

Abstract: BACKGROUNDAflatoxin B1 (AFB1) and ochratoxin A (OTA) are among the most important mycotoxins with common presence in bread and bakery products. Biological detoxification of mould food spoilage and mycotoxin contamination by lactic acid bacteria (LABs) exhibits high potential on a cost‐effective and large scale. In this work, the effect of Lactobacillus strains isolated from goat milk whey on reducing AFB1 and OTA during bread making was evaluated by the determination of mycotoxin reduction potential of 12 LAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Aflatoxin was degraded in temperatures up to 160 • C, and ochratoxin was stable in temperatures up to 180 • C [96]. A recent study demonstrated that bread contaminated with mycotoxins, aflatoxin B1, and ochratoxin A decreased the contamination percentage with a combination of LAB starter and yeast in the fermentation dough for 24 h [102]. It is noteworthy that mold can affect the sensory characteristics of bread and bring safety insecurity with mycotoxin production [95].…”
Section: Molds and Toxinsmentioning
confidence: 99%
“…Aflatoxin was degraded in temperatures up to 160 • C, and ochratoxin was stable in temperatures up to 180 • C [96]. A recent study demonstrated that bread contaminated with mycotoxins, aflatoxin B1, and ochratoxin A decreased the contamination percentage with a combination of LAB starter and yeast in the fermentation dough for 24 h [102]. It is noteworthy that mold can affect the sensory characteristics of bread and bring safety insecurity with mycotoxin production [95].…”
Section: Molds and Toxinsmentioning
confidence: 99%
“…The study by Escrivá et al [262] investigated the potential of Lactobacillus strains, specifically sourced from goat milk whey, on the biodegradation of two significant mycotoxins, AFB1 and OTA, during the bread-making process. Encouragingly, the research demonstrated that certain Lactobacillus strains can effectively reduce the levels of these mycotoxins, with L. plantarum B3 and L. paracasei B10 exhibiting the highest detoxification capabilities.…”
Section: Detoxification Of Mycotoxin By Labmentioning
confidence: 99%
“…Baking was carried out according to the methodology of Escriva et al [7,25] with some modifications, as described below. A loaf of bread was made from 100 g of flour (90 g of wheat flour type 750 and 10 g of contaminated wheat flour), 60 mL of warm water, 7 g of fresh baker's yeast, 3 g of sugar, 2 g of salt, and 2% (v/v) addition of the test yeast A. pullulans PP3 and S. podzolicus D10 suspension at a density of 5 × 10 8 cfu/mL.…”
Section: Determination Of Mycotoxin Content In Model Breadmentioning
confidence: 99%